2021
DOI: 10.1080/24721735.2021.1909865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a regional school-based mindfulness programme on students’ levels of Wellbeing and resiliency

Abstract: Mindfulness has recently shown promise in mental illness treatment and preventative contexts with school-aged young people. However, there is a shortage of studies investigating the effects of school-based mindfulness interventions on young people of a preadolescent and early-adolescent age. Therefore, the aim of the present study was to investigate the effects of a regional multi-site school-based mindfulness programme on wellbeing and resiliency in UK school children aged 9-12 years old. A total of 1,138 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(63 reference statements)
2
5
1
Order By: Relevance
“…When compared to baseline, children's self‐report emotional awareness improved after 5 weeks of attending the meditation program. This finding is consistent with findings of Devcich et al's (2017) study and Schonert‐Reichl et al's (2015) study, which all highlight the benefit of practicing meditation on enhancing the acknowledgment and acceptance of emotional experiences rather than avoiding or suppressing them (Keller et al, 2017; Nelson et al, 2022). However, the finding is inconsistent with results obtained from Britton et al's (2014) study and Vickery and Dorjee's (2016) study, which found no improvements in emotional awareness during the program.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When compared to baseline, children's self‐report emotional awareness improved after 5 weeks of attending the meditation program. This finding is consistent with findings of Devcich et al's (2017) study and Schonert‐Reichl et al's (2015) study, which all highlight the benefit of practicing meditation on enhancing the acknowledgment and acceptance of emotional experiences rather than avoiding or suppressing them (Keller et al, 2017; Nelson et al, 2022). However, the finding is inconsistent with results obtained from Britton et al's (2014) study and Vickery and Dorjee's (2016) study, which found no improvements in emotional awareness during the program.…”
Section: Discussionsupporting
confidence: 89%
“…acknowledgment and acceptance of emotional experiences rather than avoiding or suppressing them (Keller et al, 2017;Nelson et al, 2022). However, the finding is inconsistent with results obtained from exercises and repetitive habits of thinking, feeling, and acting with gratitude and kindness, children might be more familiar with the meditation techniques and incorporate the activity into their daily routine.…”
Section: Groupmentioning
confidence: 84%
See 1 more Smart Citation
“…Besides the increased incidence of symptoms of depressiveness and anxiety, fears about the future are also an important target for intervention programs. Therefore, long-term objectives for mental health care promotion should contain the implementation of school-based mental health promotion programs into standard educational practice to enhance resilience and coping skills that have been shown to positively impact the student's ability to manage daily stressors ( 58 60 ). However, implementing such programs into everyday life requires considerable time and could, e.g., first be examined for feasibility and acceptance as part of pilot projects in model regions.…”
Section: Discussionmentioning
confidence: 99%
“…Schools may then choose to implement a new prevention program that addresses the problem, but this may further increase an overlap in content areas across potentially similar interventions. For example, in recent years, new interventions have been developed to prevent youth gambling (4), reduce problem internet use (5), and promote mindful meditation (6), yet when new programs are adopted and implemented there may be little consideration given to whether the new content overlaps with existing school programming. Also, most evidence-based programs focus on specific health domains and their evaluations typically focus only on those specific behavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%